2021
DOI: 10.3390/ijms222111886
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Prolyl Oligopeptidase (POP) Inhibition in Kidney Injury Induced by Renal Ischemia–Reperfusion

Abstract: Ischemia/reperfusion injury (IRI) is a complex pathophysiological process characterized by blood circulation disorder caused by various factors, such as traumatic shock, surgery, organ transplantation, and thrombus. Severe metabolic dysregulation and tissue structure destruction are observed upon restoration of blood flow to the ischemic tissue. The kidney is a highly perfused organ, sensitive to ischemia and reperfusion injury, and the incidence of renal IRI has high morbidity and mortality. Several studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…An in depth discussion on the pathophysiological role of these enzymes falls outside the scope of the present study, but is described in recent literature [23] , [55] , [58] , [59] , [60] , [61] . Moreover, for each of these enzymes, specific pharmacological inhibitors are available, allowing more functional studies and investigations on their potential as therapeutic targets in lung diseases and COVID-19 in particular.…”
Section: Resultsmentioning
confidence: 99%
“…An in depth discussion on the pathophysiological role of these enzymes falls outside the scope of the present study, but is described in recent literature [23] , [55] , [58] , [59] , [60] , [61] . Moreover, for each of these enzymes, specific pharmacological inhibitors are available, allowing more functional studies and investigations on their potential as therapeutic targets in lung diseases and COVID-19 in particular.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB appears to have a pro-inflammatory function in the lung resulting in neutrophilic infiltration and pulmonary edema [ 13 ]; moreover, it has been shown that PREP regulate the NF-κB pathway [ 16 ]. Therefore, in this study, we confirmed in vivo the modulation of NF-κB pathway by Western Blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The immunohistochemical localization was executed as previously described [ 19 ]. In brief, all slides were incubated overnight using the following primary antibody: anti-Glutamate receptor (NMDAR2B) (1:100; Thermofisher, Waltham, MA, USA; # MA1-2014).…”
Section: Methodsmentioning
confidence: 99%